Evolution of stress fields during crack growth and arrest in a brittle-ductile CrN-Cr clamped-cantilever analysed by X-ray nanodiffraction and modelling. (15th January 2021) - Meindlhumer, M.; Brandt, L.R.; Zalesak, J.; Rosenthal, M.; Hruby, H.; Kopecek, J.; Salvati, E.; Mitterer, C.; Daniel, R.; Todt, J.; Keckes, J.; Korsunsky, A.M.
Abstract: In order to understand the fracture resistance of nanocrystalline thin films, it is necessary to assess nanoscopic multiaxial stress fields accompanying crack growth during irreversible deformation. Here, a clamped cantilever with dimensions of 200 × 23.7 × 40 μm 3 was machined by focused ion beam milling from a thin film composed of four alternating CrN and Cr layers. The cantilever was loaded to 460 mN in two steps and multiaxial strain distributions were determined by in situ cross-sectional X-ray nanodiffraction. Characterization in as-deposited state revealed the depth variation of fibre texture and residual stress across the layers. The in situ experiment indicated a strong influence of the residual stresses on the cross-sectional stress fields evolution and crack arrest capability at the CrN-Cr interface. In detail, an effective negative stress intensity of −5.9 ± 0.4 MPa m ½ arose as a consequence of the residual stress state. Crack growth in the notched Cr layer occurred at a critical stress intensity of 2.8 ± 0.5 MPa m ½ . The results were complemented by two-dimensional numerical simulation to gain further insight into the elastic-plastic deformation evolution. The quantitative experimental and modelling results elucidate the stepwise nature of fracture advancement across the alternating brittle and ductile layers and their interfaces. Graphical abstract: Unlabelled Image Highlights: Multi-axial residual stress distributions across a notched CrN-Cr clamped micro-cantilever were determined experimentally. Residual stresses in Cr introduce an effective stress intensity of −5.9 ± 0.4 MPa m ½, forming a plastic zone around the notch. Upon crack growth through Cr to the adjacent CrN-Cr interface, the crack is arrested there and its stress fields disappears.